ANALISIS SEBARAN SEDIMEN BERDASARKAN UKURAN BUTIR DAN NILAI SORTASI DI PERAIRAN PULAU DUTUNGAN KABUPATEN BARRU SULAWESI SELATAN - Hasriyanti, Hasriyanti (Teknosains: Media Informasi Sains dan Teknologi, 2015)
This study aims to determine the distribution of sediments based on the type of grain and sorting values in the waters of the island Dutungan Barru. Seabed sediment sampling was also carried out by using a bottom grab samples were performed at each station. Note the position and time pengamatan.Sampel drawn on the bottom sediment grab samples inserted into the sediment sample bag and labeled. Laboratory analysis to determine the type, grain size / diameter of the bottom waters. Field data collection activities carried out at 12 sampling points, but there are two points that did not work because the bottom waters sampled in the form of hard coral, making it very difficult for the presence of basic sediment samples waters. The results showed that the characteristics of the sediment on the island consists of silt Dutungan greatest on Observation Station 4 with a value of 0.09 grams sorting medium, very fine sand to the largest measurement station 8 at 8.20 grams with sorting pretty good value, fine sand on measurement station 9 at 56.02 grams with sorting value ugly, sand is being greatest at Observation Station 1 at 58.28 grams with sorting pretty good value, most large coarse sand on Observation Station 5 at 54.11 grams with a very good value, very coarse sand greatest at 8 Observation Station at 21.84 grams with sorting pretty good value, and most large gravel on Observation Station 7 of 63.5 grams with moderate sorting value. On the Measurement Station 1 is dominated by sand sediment medium (0.25 to 0.85 mm) although containing fine sand (0.15 to 0.25 mm) and silt (<0.15 mm) higher than the measurement station other. This is due to its location further away from the beach and sheltered from the effects of ocean waves and the number of organic matter and detritus that brought water to accumulate in the waters of this river, especially at lower currents.